The second approximation in a small parameter to a solution of the problem of elastoplastic instability of a rotating disk - Lila, D.M. (Reports of the National Academy of Sciences of Ukraine, 2018)
We have proposed a way of the investigation of the possible loss of stability by a rotating thin circular disk by the method of small parameter on the basis of Saint-Venant's yield condition. We have obtained a characteristic equation for the critical radius of the plastic zone as the second approximation. We also have found the critical angular rotational velocity.